Exploring the Mechanism of the Palladium-Catalyzed 3-Butene-2-ol Amination Reaction: A DFT Study - Lyu, Lingshan; Feng, Wei; Yang, Siwei; Liu, Huiling; Huang, Xuri (Frontiers in Chemistry, 2020)
Palladium-catalyzed asymmetric allylic substitution, due to its valuable reactive profile, has become a quite useful tool in organic synthesis fields. In the present study, density functional theory (DFT) calculations were applied to investigate the important factors for Palladium-catalyzed 3-butene-2-ol and methylaniline amination reaction, with THF as solvent. We find this catalytic protocol exists high regio- and stereoselectivity, which is in line with the experimental result. According to our calculations, the high regio- and stereoselectivity is caused by the steric hindrance between the substrate and the catalyst ligand. To verify this point, we further explore the reactive process with different axial chirality on the catalyst ligand (altering the steric hindrance), and the results suggest that the preponderant R chiral configuration product has reversed. These results could lead a better understanding of the mechanism for 3-butene-2-ol amination reaction, and are helpful for the design of the corresponding catalyst ligand in the industry.